BENTUK DAN MAKNA RUMAH TINGGAL ETNIS TIONGHOA DI BANJARMASIN - Kurnia Widiastuti; Anna Oktaviana (INFO-TEKNIK, 2015)
Settlement of ethnic Chinese in Banjarmasin tend to be concentrated in the large waterways, namely in the area of Veterans, Gedangan, and RK Ilir who all along the river Martapura. In general, the ethnic Chinese community living in Banjarmasin, build and inhabit their home by adjusting the environment and local culture that has been there, so many who live in the traditional banjar-type house (traditional house banjar). In a further development of life between cultures and behavior of a relationship of mutual influence.  This study aimed to identify the forms and meanings (of the form) homes ethnic Chinese in Chinatown Banjarmasin. Selected case studies are some of the homes were inhabited by ethnic Chinese in the form of Banjar traditional house in the Chinatown area of Banjarmasin.This research uses descriptive analytical method, which describe the characteristics of the dwelling as an object of study, looking for the type of home Banjar close similarity, and identification of native cultural elements is indicative of acculturation China with Banjar culture. In this context, architecture is understood as part of the totality of social systems associated with other socio-cultural variables.  The analysis was performed by comparing the typology few homes with a shape that resembles a traditional house Banjar, then analyzing the pattern of the layout, style and style, ornaments, as well as the construction of the structure.The analysis showed that the basic form of house Banjar still maintained by ethnic Chinese who inhabit it, because of the assumption of symmetry meaning in Chinese architecture. Ornaments and color elements in Chinese architecture, which blend in with the architecture of Banjar architecture make Chinatown in London came up with a different character from Chinatown in Indonesia in general. What is more important is that all these elements exist in Chinese people's homes loaded with meaning and symbolic message about the meaning of community life and prosperity in the world related to the traditions and beliefs of Chinese society at large. Keywords  :  settlement, ethnic chinese and traditional house banjar